Back in The Dark Ages: Role of Intuition in The Decision-Making Processes - Andrzej Z. Wlodarczyk (Journal of Management Research, 2025)
Cornucopia of emerging information far exceeds any one’s ability to confront the emerging issues today. Isaac Newton’s emphasis on linear clockwise universe in which all principles of the known world could be understood through rational faculties pushed subconscious intuition to the side as superstitious not worthy of academic pursuit. Merely three hundred years later, digital revolution embraced intuition’s long-lost appeal. Today’s technology granted humanity the opportunity to collect infinite amount of information. Again, intuition is being espoused as an alternative to a rational decision-making model. Following science three-hundred-year-long love affair with reason and logic, humanity is back where it started–in the dark ages. Albert Einstein’s theory of relativity associated with complexity and use of nonlinear concepts such as intuition and emotions have become a common corporate practice. Even though human mind retained its rational capacities, the world in which decisions are made today has changed.